Relations Of Family Planning Services By Selection of Intrauterine Contraceptives In High Coverage and Low Coverage Areas - darmayanti, Rofik; Betristasia Puspitasari (Jurnal EduHealth, 2023)
One of the reasons of the decreasing in using IUD is caused by factors of health services, while the quality of health services is influenced by several factors, such as: the procedures, the health workers, the costs and the facilities. The purpose of this study is to analyze the correlation between the factors of family planning services (in terms of procedures, health workers, cost, facilities, information) with the selection of an intrauterine device and to analyze the differences of family planning services factors with the selection of an intrauterine device in areas of high and low coverage. The type of this research is a comparative study of analytical with crosssectional approach, data were collected using questionnaires. Research subjects were 303 fertile age couples who became new acceptors, extracted by proportionate Stratified Random Sampling technique. The research was conducted in the region of Kediri June-August 2020. The results of data analysis using the chi-square test showed that of the six aspects of family planning services (procedures, health workers, cost, facilities and information) in the high coverage area and in low coverage area that had correlation with the selection of an intrauterine device was the aspect of procedure and health workers, with value of p <0.05. In the two regions chosen, it was found significant differences in the procedures, cost and information aspects with value p <0.05, while for aspects of health workers, facilities and quality there was no significant difference with values p > 0.05. Conclusion, there is a relation between the factors of family planning services toward the aspects of procedures of family planning services, workers of family planning services, costs of family planning services, and information of family planning services with the selection of an intrauterine device. There is a different in areas of high and low coverage toward the aspects of procedures of family planning services, costs of family planning services, and information of family planning services.